PHYSICS EDUCATION STUDENTS’ NEED ANALYSIS TOWARD ENGLISH TEACHING MATERIAL - Rahman, Indah Fadhilah; Rukmana, Alia Putri (ETERNAL (English, Teaching, Learning, and Research Journal), 2022)
English Specific Purpose (ESP) is a subject on teaching English to Physics Education students. The goal of this study is to determine what the target needs and English learning needs are for students in the Physics Education Department at UIN Alauddin Makassar. The survey method applied in this study as the research design. The researcher used questionnaires and interviews to gather information for this study. This study included 56 participants, including 50 third-semester students from the 2019 intake year, one lecturer, and five graduates from the Physics Education Department at UIN Alauddin Makassar. Microsoft Excel was used to examine the data. The findings of this study revealed that students need to learn speaking, reading, and writing skills, because those are important to support them to succed in stujdy. It imply that the material should covers those skills to fullfill the students’ needs.